2011
DOI: 10.1097/aog.0b013e31822545a9
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Delivery After External Cephalic Version and the Risk for Cesarean Delivery

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
2
7
1
Order By: Relevance
“…Similar differences in caesarean section rate was also noted previously in another study (4% versus 34%) [10]. The reasons for increased need for IOL and for the increase in caesarean section remain unclear [15]. Several possible reasons include inability of a breech baby to tolerate stress during labour (in which case there would be higher rate for fetal distress which we did not show (only 2 of the 13 sections were due to fetal distress), some uterine muscle abnormality that predisposed to breech presentation in the first instance and an unmolded unengaged fetal head, both of which may predispose to dystocia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar differences in caesarean section rate was also noted previously in another study (4% versus 34%) [10]. The reasons for increased need for IOL and for the increase in caesarean section remain unclear [15]. Several possible reasons include inability of a breech baby to tolerate stress during labour (in which case there would be higher rate for fetal distress which we did not show (only 2 of the 13 sections were due to fetal distress), some uterine muscle abnormality that predisposed to breech presentation in the first instance and an unmolded unengaged fetal head, both of which may predispose to dystocia.…”
Section: Discussionsupporting
confidence: 84%
“…While some [15] [16] have not seen such an increase, a meta analysis [17] of several studies has noted a two fold increase in CS rate after a successful ECV and this was independent of any increased induction rate. A recent study from Canada [18] also reported a Caesarean section rate in such women of 15% versus 6.0% in women with cephalic presentation from the onset and noted that nulliparity and induction of labour were associated with caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the time elapsed between ECV and delivery was not different between nulliparous and multiparous patients in the study group who had a CD, or between patients who had vaginal delivery and patients who had CD. Thus, the time duration between ECV and delivery could not explain the higher rate of CD as suggested in a previous study [49].…”
Section: Discussionmentioning
confidence: 66%
“…A retrospective cohort study of 483 successful ECV cases showed that the incidence of cesarean delivery is increased in both primiparous and multiparous women who deliver within 96 hours of the ECV (adjusted OR, 2.54; 95% CI, 1.36-4.72). 29 The authors propose that this observation may be related to the unengaged fetal head after a successful ECV, predisposing to labor dystocia and cord prolapse during labor. 29 Furthermore, if ECV is performed in the early term period, immediate induction of labor may lead to the well-described perinatal complications associated with early term delivery and is generally discouraged.…”
Section: Management Of Fetal Malpresentation 249mentioning
confidence: 97%